The spirit of populism political theologies in polarized times - Schmiedel, Ulrich 1985-; Ralston, Joshua ca. 20./21. Jh (Brill, 2022)
"Populism is a buzzword. This compilation explores the significance of religion for the controversies stirred up by populist politics in European and American contexts in order to understand what lies behind the buzz. Engaging Jewish, Christian, and Islamic political thought and theology, contributions by more than twenty established and emerging scholars explore right-wing and left-wing protests, offering critical interpretations and creative interventions for a polarized public square. Both methodologically and thematically, the compilation moves beyond essentialist definitions of religion, encouraging a comparative approach to political theology today"
Keywords: Politische Theologie; Populismus; Populism / Religious aspects; Populism / Europe; Populism / United States; Political theology / Great Britain; Political theology / United States; Political theology; Populism; Europe; Great Britain; United States; Aufsatzsammlung